An asymmetric cointegration approach of foreign portfolio investment-growth nexus - Duasa, Jarita (Serials Publications (New Delhi, India), 2011)
The present study attempts to analyze the long-run equilibrium relationship between foreign portfolio investment (FPI) and real Gross Domestic Product (GDP) by cointegration tests assuming asymmetric adjustment. Following Enders and Siklos (2001), the Engle-Granger two-step cointegration test is expanding to incorporate an asymmetric error correction term. It is found that there exists asymmetric cointegration between foreign portfolio investment inflow and real GDP, when momentum-threshold autoregressive (M-TAR) model is conducted. However, the asymmetric cointegration is not existence using threshold autoregressive (TAR) model. From estimation of M-TAR error-correction model, the adjustment back to equilibrium is more significant following relative decrease in real GDP (below long-run value). The results reflect the evidence of persistence low economic growth contributed by decrease in FPI inflow, in the case of Malaysia, as the real GDP adjustment to its long-run value is quite slow. The findings signify the use of capital controls by the authority during the 1997 Asian financial crisis to shield the country from the shock of FPI inflow and obviously, precautionary measures must be well-formed against any serious threat from inflows of short-term capital in the future.